A Batch Task Migration Approach for Decentralized Global Rescheduling - Freitas, Vinicius; Santana, Alexandre de L.; Castro, Márcio; Pilla, Laércio L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Effectively mapping tasks of High Performance Computing (HPC) applications on parallel systems is crucial to assure substantial performance gains. As platforms and applications grow, load imbalance becomes a priority issue. Even though centralized rescheduling has been a viable solution to mitigate this problem, its efficiency is not able to keep up with the increasing size of shared memory platforms. To efficiently solve load imbalance today, and in the years to come, we should prioritize decentralized strategies developed for large scale platforms. In this paper, we propose our Batch Task Migration approach to improve decentralized global rescheduling, ultimately reducing communication costs and preserving task locality. We implemented and evaluated our approach in two different parallel platforms, using both synthetic workloads and a molecular dynamics (MD) benchmark. Our solution was able to achieve speedups of up to 3.75 and 1.15 on rescheduling time, when compared to other centralized and distributed approaches, respectively. Moreover, it improved the execution time of MD by factors up to 1.34 and 1.22 when compared to a scenario without load balancing on two different platforms.